Application of low cost ionic liquids for the separation of glycerine from palm oil-based biodiesel - Hashim, M.A.; Mjalli, F.S.; Hayyan, M.; Al-Nashef, I.M. (2009)
One of the most serious obstacles in using biodiesel as an alternative fuel is the intricate and costly purification processes involved in its production. The difficulties in the separation of glycerine and other reaction mixtures necessitate the development of new competent low cost separation processes. In the present work, a low cost quaternary ammonium salt-glycerinebased ionic liquid is used as a solvent for extracting glycerine from the transesterification biodiesel product. The separation technique was tested on palm oil-based biodiesel. The laboratory-scale purification experiments established the viability of the technique as the purified biodiesel fulfilled the EN 14214 and ASTM D6751 standard specifications for biodiesel fuel in terms of glycerine content.